The thickening of carbon fibers via a 3D island growth mechanism: New insights from a theoretical and experimental study. (November 2019) - Wan, Wubo; Gunning, James; Lee, Woo Jin; Li, Chao'en; Hao, Xiaojuan; Zhao, Zongbin; Qiu, Jieshan; Patel, Jim
Abstract: A simple geometric model of 3D island growth has been applied to simulate the thickening of fibers by pyrolytic carbon. This model identifies the parameters that influence morphological features of vapor thickened fibers, such as the extent of crenulation and the degree of asymmetry, and provides a rational explanation for a wide variety of carbon-based structures. An experiment involving the deposition of pyrolytic carbon on pre-formed silicon-based fibers is used to demonstrate the ability of the model to predict the morphological features.